Effect of Trunk Support on Upper Extremity Function in People With Chronic Stroke and People Who Are Healthy. Issue 8 (1st August 2015) - Wee, Seng Kwee; Hughes, Ann-Marie; Warner, Martin B.; Brown, Simon; Cranny, Andy; Mazomenos, Evangelos B.; Burridge, Jane H.
Abstract : Background: Trunk control is thought to contribute to upper extremity (UE) function. However, this common assumption in neurorehabilitation has not been validated in clinical trials. Objective: The study objectives were to investigate the effect of providing external trunk support on trunk control and UE function and to examine the relationship between trunk control and UE function in people with chronic stroke and people who were healthy. Design: A cross-sectional study was conducted. Methods: Twenty-five people with chronic stroke and 34 people who were healthy and matched for age and sex were recruited. Trunk control was assessed with the Trunk Impairment Scale (TIS), and UE impairment and UE function were assessed with the UE subsection of the Fugl-Meyer Assessment (FMA-UE) and the Streamlined Wolf Motor Function Test (SWMFT), respectively. The TIS and SWMFT were evaluated, with and without external trunk support; the FMA-UE was evaluated without trunk support. Results: With trunk support, people with stroke showed improvement from 18 to 20 points on the TIS, a reduction in SWMFT performance times from 37.20 seconds to 35.37 seconds for the affected UE, and improvement from 3.3 points to 3.4 points on the SWMFT Functional Ability Scale for the function of the affected UE. With trunk support, the SWMFT performance time for people who were healthy was reduced from 1.61 seconds to 1.48 seconds for the dominant UE and from 1.71 seconds to 1.59 seconds for the nondominant UE. A significant moderate correlation was found between the TIS and the FMA-UE ( r =.53) for people with stroke. Limitations: The limitations included a nonmasked assessor and a standardized height of the external trunk support. Conclusions: External trunk support improved trunk control in people with chronic stroke and had a statistically significant effect on UE function in both people with chronic stroke and people who were healthy. The findings suggest an association between trunk control and the UE when external trunk support was provided and support the hypothesis that lower trunk and lumbar stabilization provided by external support enables an improvement in the ability to use the UE for functional activities.